Optical Design of Dilute Nitride Quantum Wells Vertical Cavity Semiconductor Optical Amplifiers for Communication Systems - Chaqmaqchee, Faten A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2016)
III-V semiconductors components such as Gallium Arsenic (GaAs), Indium Antimony (InSb), Aluminum Arsenic (AlAs) and Indium Arsenic (InAs) have high carrier mobilities and direct energy gaps. This is making them indispensable for today’s optoelectronic devices such as semiconductor lasers and optical amplifiers at 1.3 μm wavelength operation. In fact, these elements are led to the invention of the Gallium Indium Nitride Arsenic (GaInNAs), where the lattice is matched to GaAs for such applications. This article is aimed to design dilute nitride GaInNAs quantum wells (QWs) enclosed between top and bottom of Aluminum (Gallium) Arsenic Al(Ga)As distributed bragg mirrors (DBRs) using MATLAB® program. Vertical cavity semiconductor optical amplifiers (VCSOAs) structures are based on Fabry Perot (FP) method to design optical gain and bandwidth gain to be operated in reflection and transmission modes. The optical model gives access to the contact layer of epitaxial structure and the reflectivity for successive radiative modes, their lasing thresholds, emission wavelengths and optical field distributions in the laser cavity.